Analysis of Students' Needs for Guidance and Counseling Services Based on Personal, Social, Academic, and Career Competency Standards - Anne Hafina (Universitas Pendidikan Indonesia (UPI), 2024)
Learners can be said as individuals who are in the process of developing their attitudes, abilities, and knowledge. In the process, this development does not always reach an optimal degree, even developmental stagnation, personality problems, or behavioral deviations can occur. In this case, guidance and counseling services for students can be pursued as an effort to prevent students from developing in unexpected directions. However, the effectiveness of this effort can be realized if the service provider can identify students' needs for guidance and counseling services based on aspects of personal, social, academic, and student career competency standards. Therefore, this study aims to describe the results of the analysis of students' needs for guidance and counseling services based on these three aspects. This needs analysis has been carried out in the first year of research. The research method used is a quantitative research approach with a descriptive-analytic method. This research was conducted in two cities and two districts in West Java Province (Bandung City, Bandung Regency, Cimahi City, and West Bandung Regency). The research population was all students from class VII to class XII. The research subjects involved included experts, practitioners, and junior and senior high school students.